Afterwork Concert No. 3, “Mit veränderten Reprisen” - Zafeiropoulos, Anastasios (Koetshuis, Ghent Orpheus Instituut, 2024)
Program: G. S. Löhlein, Sonata in C minor, 1765
Performing on clavichord and fortepiano, Tom Beghin explores a once lively practice of varying repeats through two sets of keyboard sonatas—for a total of twelve, to be digested in groups of three: CPE Bach’s Sechs Sonaten mit veränderten Reprisen, Wq 50 (1760) and Mozart’s six “Munich” Sonatas K 279–285 (1774–75).
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850